IMPROVING STUDENTS’ SPEAKING SKILL THROUGH GROUP INVESTIGATION TECHNIQUE AT XI IPA 2 STUDENTS’ OF SMA NEGERI 1 KOTA SORONG - Marissa S Tupamahu; Vantri Pieter Kelelufna (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2022)
This research used the group investigation technique to improve students’ speaking skills. The subject of this research was the XI IPA 2 of SMA Negeri 1 Kota Sorong, which consisted of 35 students. This study employed